A multiple mediation model of trait worry and hazardous drinking among treatment-seeking smokers: the roles of coping and conformity drinking motives. Issue 5 (2nd September 2020) - Hallford, Gerald; Bakhshaie, Jafar; Rodriguez-Cano, Ruben; Shepherd, Justin M.; Schmidt, Norman B.; Zvolensky, Michael J.
ABSTRACT: Alcohol use is associated with poorer smoking cessation-related outcomes, and smokers with elevated levels of worry experience greater smoking cessation problems. Yet, little is known about the explanatory mechanisms that may underlie the relationship between trait worry and hazardous drinking among smokers. Therefore, this study explored the explanatory roles of coping and conformity drinking motives in the relationship between trait worry and hazardous drinking outcomes including alcohol consumption, alcohol problems, maximum number of drinks, and the number of prior alcohol quit attempts among treatment-seeking smokers. Participants included 377 treatment-seeking smokers who consumed at least one alcoholic drink in the last year (48% female; 86.2% Caucasian; M age = 34.83 years, SD = 13.38). Results showed a significant indirect effect of trait worry through coping-related drinking motives in relation to alcohol consumption, alcohol problems, maximum number of drinks, and number of prior drinking quit attempts. These findings were evident after controlling for gender, cigarette dependence, and current psychopathology. These findings suggest that coping drinking motives are one mechanism that may explain the relation between trait worry and hazardous drinking outcomes among treatment-seeking smokers.